288 LAY LADY LAY, A TRICKY CASE OF PLATYPNEA ORTHODEOXIA SYNDROME. (15th December 2022) - Coraducci, Francesca; Barbarossa, Alessandro; Manfredi, Roberto; Coretti, Francesca; Torselletti, Lorenzo; Belleggia, Sara; Paolini, Federico; Alfieri, Michele; Brugiatelli, Leonardo; Bastianoni, Gianmarco; Principi, Samuele; Ciliberti, Giuseppe; et al.
Abstract: Platypnea orthodeoxia syndrome (POS) is characterized by dispnoea and a fall in oxygen saturation levels when in the upright position that resolves lying down in the supine position. It is secondary to a right to left shunt (R-L shunt), typically trough a patent foramen ovale (PFO). Normally, in the presence of a PFO, R-L shunt does not occur unless there is a clinical condition that raises right side pressures like venous thromboembolism, hydrothorax, pneumothorax or chronic pulmunary hypertension. Although its physiopathological mechanisms are not entirely understood, in the POS, R-L shunt mostly occurs due to anatomical alteration of the interatrial septum in the upright position. Venous flow therefore can pass from the inferior vena cava through the PFO or an atrial septal defect (ASD) to the left side of the heart. We present a case of a 77 y.o. woman with no relevant past medical hystory, that was admitted to hospital care because of a mild pulmonary embolism and deep vein trombosis of the right popliteal vein. She was promptly treated for PE with direct oral anticoagulation achieving the resolution of the embolism. Despite the CT scan showed the complete resolution of the embolism her dysponoea did not improve. Her blood gas analysis showed normocapnic hypoxiemic respiratory insufficiency with a suspicious lowering of oxygen saturation levels when in the upright position which however improved in the supine position. She also had a transient episode of dysarthria and hypostenia to the right upper limb, the negative head CT scan was suggestive of a transient ischaemic attack. A pulmonary scintigraphy showed arterious renal perfusion as in a right to left shunt. She then underwent a transoesophageal echocardiography which showed an hypermobile interatrial septum with evidence of a patent foramen ovale with left to right shunt. The exame was in fact executed in the supine position. Given these findings, we concluded for a diagnosis of POS. Because of this records, the severity of the shunt and the suggestive clinical hystory of ortodeoxya she underwent PFO closure positioning an Amplatzer PFO Occluder 25 mm. The procedure was carried out without complications and led to complete resolution of the symptoms and the signs of platipnoea-ortodeoxya.